Angiotensin-converting enzyme I/D polymorphism and acute respiratory distress syndrome. (December 2015) - Deng, Xingqi; Zhang, Shaokun; Jin, Kun; Li, Lanyan; Gu, Wei; Liu, Mei; Zhou, Ling
Background: Some studies have assessed the association between angiotensin-converting enzyme (ACE) I/D polymorphism and acute respiratory distress syndrome (ARDS) risk. However, the results have been inconclusive and contradictory. Therefore, we performed a meta-analysis to investigate the association between ACE I/D polymorphism and ARDS risk. Methods: All relevant studies were searched using PubMed and EMBASE. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were estimated using random-effects models or fixed-effects models. Results: A total of 14 studies with 5218 subjects were included in this meta-analysis. We found that ACE I/D polymorphism significantly associated with an increased ARDS risk (OR=1.57; 95% CI 1.30–1.89; P <0.00001). In the subgroup analysis by race, Caucasians with ACE I/D polymorphism showed increased ARDS risk (OR=1.63; 95% CI 1.32–2.02; P <0.00001). However, Asians with this polymorphism did not show significantly increased ARDS risk (OR=1.31; 95% CI 0.90–1.90; P =0.95). In the subgroup analysis by age group, adults showed increased ARDS risk (OR=1.60; 95% CI 1.32–1.93; P <0.00001), while pediatric patients did not have increased ARDS risk (OR=1.15; 95% CI 0.57–2.30; P =0.70). Conclusions: This meta-analysis suggested that ACE I/D polymorphism might contribute to the susceptibility for ARDS.